Vida de anaquel del tomate (Solanum lycopersicum l.) aplicando un recubrimiento comestible de quitosano y muyuyo - Rodríguez Molina, Junior Geovanny (2022)
The tomato is a perishable agricultural product that requires post-harvest treatments to prolong its useful life, thus the objective of the research was to determine the period of time in which the quality attributes of the tomato (Solanum lycopersicum l.) are preserved by applying formulations of an edible coating based on chitosan and muyuyo; a Completely Randomized Block Design (Days) was used in a bifactorial arrangement A*B. Factors A were studied: chitosan concentration (1.0 and 1.5%) and factor B: muyuyo concentration (40 and 60%) plus a control (without coating), the experimental samples were stored at room temperature (23 -25ºC) for 20 days. The variables that were evaluated were: acidity, soluble solids, weight loss, maturity index, microbial stability (mesophilic aerobes and molds and yeasts) and sensory quality using a hedonic scale. The combinations of both factors did not show significant effects p>0.05 compared to the control, regarding the conservation of the physical-chemical and sensory characteristics evaluated, likewise, they did not show inhibition against any strain of microorganism. The blocking factor (days) turned out to be significant in view of the physical-chemical characteristics of all the treatments, changing continuously between the analysis periods. Likewise, the highest concentration of factor A (chitosan concentration 1.5%) showed an effect on the maturity index variable. Finally, it was determined that the concentrations of chitosan (1 and 1.5%) and muyuyo (40 and 60%) applied did not extend the shelf life of tomatoes.